POST-PANDEMI COVID-19 ECONOMIC RECOVERY - Adrian, Adrian; Wibowo, Kuncoro; Sarjana, Samuel Horas (Jurnal Manajemen & Bisnis Jayakarta, 2022)
Covid-19 is impacting the whole country including Indonesia, the ever-increasing distribution of covid-19 is causing economic growth pressures. Indonesia's economic growth ranged from -2.1% yoy by 2020, placing Indonesia in fourth place, after Vietnam, China and South Korea. Indonesia's economic contraction is relatively moderate, one of the smallest between the G-20 and ASEAN. Impact on the economic sector due to the covid-19 pandemic in Indonesia, among others, the occurrence of layoffs, decreased imports, rising prices (inflation) as well as losses in the tourism sector that led to a decrease in occupancy. Economic policy in the form of relaxation of economic policy is expected to increase purchasing power and economic movement in all areas.